THE IMPORTANCE OF AUTHENTIC MATERIALS TO ENHANCE LISTENING COMPETENCE (International journal of artificial intelligence, 2025)
This article explores the significance of authentic materials in enhancing listening competence. The use of authentic materials is essential in enhancing listening abilities, particularly in language learning and communication skills development. Authentic materials refer to resources created for real-life communication rather than for educational purposes, such as podcasts, news broadcasts, films, and conversations. These materials offer learners exposure to natural language, diverse accents, colloquial expressions, and contextual usage that are often absent in traditional learning materials. By engaging with authentic materials, learners not only improve their listening comprehension but also gain insights into cultural nuances and practical language usage. This approach fosters a more immersive learning experience, enabling learners to adapt to varied speaking styles and contexts they are likely to encounter in real-world situations.